2013
DOI: 10.2147/opth.s51600
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of studies on cosmetically tinted soft contact lenses

Abstract: BackgroundConcerns regarding the safety of cosmetically tinted contact lenses have been reported in the literature. The purpose of this paper is to evaluate the safety of cosmetically tinted contact lenses in a large number of patients across six clinical trials that varied from 1 week to 3 months in duration.MethodsLenses tested included: Naturelle limbal ring daily disposable, Lacelle limbal ring daily disposable, Lacelle colored cosmetic daily disposable, Lacelle limbal ring planned replacement at 2 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…In most Asian countries, approximately one-third of all contact lens wearers use decorative tinted soft contact lenses and the market share for this segment has contributed significantly to the rapid growth 1 2. A decorative tinted soft contact lens contains a central pigment-free optical zone and a peripheral pigment-tinted area.…”
Section: Introductionmentioning
confidence: 99%
“…In most Asian countries, approximately one-third of all contact lens wearers use decorative tinted soft contact lenses and the market share for this segment has contributed significantly to the rapid growth 1 2. A decorative tinted soft contact lens contains a central pigment-free optical zone and a peripheral pigment-tinted area.…”
Section: Introductionmentioning
confidence: 99%
“…Since they are classified as medical devices in the USA, purchasing CCL requires a prescription. However, as they are worn solely for cosmetic purposes, users may incorrectly assume that consultation with an eye care professional is not required 2,5. As a result, users may purchase CCL from vendors who are not licensed to sell contact lenses or may obtain them from friends or family members 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…However, as they are worn solely for cosmetic purposes, users may incorrectly assume that consultation with an eye care professional is not required 2,5. As a result, users may purchase CCL from vendors who are not licensed to sell contact lenses or may obtain them from friends or family members 5,6. Little is known about these practices, however, as almost no studies have been conducted on this topic 6.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of cosmetic CLs is controversial. More speci cally, there have been several negative reports about adverse events related to the use of DCLs [3][4][5].A recently published meta-analysis that was conducted by a manufacturing company about their own products summarized six, unpublished results regarding the safety of their DCLs and concluded that they were safe [6]. This report, as written, would be insu cient as a meta-analysis document because it did not provide the calculation of pooled odds ratios or relative risk assessment.…”
Section: Introductionmentioning
confidence: 99%